Aceria (Acarina: Eriophyoidea) in Taiwan: five new species and plant abnormalities caused by sixteen species - Huang, Kun-Wei (Zootaxa, 2008)
In this study, 16 species of Aceria Keifer, 1944, including 5 new species and 4 new records, causing visible damage to plants in Taiwan, are described. They are: Aceria litchii (Keifer, 1943) infesting Litchi chinensis and Dimocarpus longana; Aceria sacchari Wang, 1964 infesting Saccharum officinarum; Aceria spicati (Stebbins, 1909) infesting Aceria morrisonense and Acer kawakamii; Aceria kuko (Kishida, 1927) infesting Lycium chinense; Aceria pipturi Keifer, 1966 infesting Pipturus arborescens; Aceria eriobotryae (Keifer, 1938) infesting Eriobotrya japonica; Aceria litseae (Keifer, 1972) infesting Litsea hypophaea; Aceria gallae T. Huang, 1996 infesting Cordia dichotoma; Aceria pobuzii Huang, 1996 infesting Cordia dichotoma; Aceria shepherdiae Keifer, 1966 infesting Elaeagnus thunbergii; Aceria roxburghianae sp. nov. infesting Rhus chinensis roxburghiana; Aceria mikaniae (Nalepa, 1918) infesting Mikania cordata; Aceria virosae sp. nov. infesting Flueggea virosa; Aceria serratifoliae sp. nov. infesting Premna serratifolia; Aceria sylvestrae sp. nov. infesting Elaeocarpus sylvestris and Aceria taiwanensis sp. nov. infesting Vitex trifolia. A key to the 20 species of Aceria in Taiwan is provided.